Switching of Techniques and Consumption Per Head: An Economic Clarification - Bruno, Michael; Burmeister, Edwin; Sheshinski, Eytan (Quarterly Journal of Economics, 1970)
Michael Bruno, Edwin Burmeister, Eytan Sheshinski; Switching of Techniques and Consumption Per Head: An Economic Clarification, The Quarterly Journal of Ec